2021
DOI: 10.1111/eip.13217
|View full text |Cite
|
Sign up to set email alerts
|

Introducing the youth residential rehabilitation service: An operational and experiential overview of a psychosocial residential support option for young people experiencing mental health challenges

Abstract: Aim: A range of residential supports is available for young people experiencing mental health challenges. One Australian example is the Youth Residential Rehabilitation Service, which provides up to 12 months of intensive psychosocial support in a residential setting to young people aged 16-25 experiencing serious mental health challenges. This paper aimed to add to the scant literature on these services, describing the experiences of young people and staff members across the duration of a stay.Methods: This s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…Spies et al (2022a, 2022b, 2022c) findings were reinforced by the outcomes of the current study, which found that young people valued the supportive role that the RFUP played in facilitating positive relationships with their workers. Furthermore, the findings of this study support outcomes described by the YYRs report that young people learn to become experts of themselves via valuing diverse knowledge (Spies et al , 2022a, 2022b, 2022c). The RFUP, by valuing the young persons’ own expertise and knowledge, facilitates a process whereby young people gain a deeper understanding of themselves.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…Spies et al (2022a, 2022b, 2022c) findings were reinforced by the outcomes of the current study, which found that young people valued the supportive role that the RFUP played in facilitating positive relationships with their workers. Furthermore, the findings of this study support outcomes described by the YYRs report that young people learn to become experts of themselves via valuing diverse knowledge (Spies et al , 2022a, 2022b, 2022c). The RFUP, by valuing the young persons’ own expertise and knowledge, facilitates a process whereby young people gain a deeper understanding of themselves.…”
Section: Discussionsupporting
confidence: 72%
“…A recent report describing the practice approach and outcomes for the MHCSS’s YRR service (Spies et al , 2022a, 2022b, 2022c) highlighted the importance of relational factors between young people and workers. Spies et al (2022a, 2022b, 2022c) findings were reinforced by the outcomes of the current study, which found that young people valued the supportive role that the RFUP played in facilitating positive relationships with their workers. Furthermore, the findings of this study support outcomes described by the YYRs report that young people learn to become experts of themselves via valuing diverse knowledge (Spies et al , 2022a, 2022b, 2022c).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Young people continue to receive specialist supports through other service systems and some participate in education or employment. This service type is explained further in a complementary article (Spies et al, 2021).…”
Section: Methodsmentioning
confidence: 99%